Intramuscular Injection of Adenoassociated Virus Encoding Human Neurotrophic Factor 3 and Exercise Intervention Contribute to Reduce Spasms after Spinal Cord Injury. (11th March 2019) - Chang, Yu-Xin; Zhao, Yan; Pan, Su; Qi, Zhi-Ping; Kong, Wei-Jian; Pan, Yi-Ran; Li, Hong-Ru; Yang, Xiao-Yu
Abstract : Limb spasms are phenomena of hyperreflexia that occur after spinal cord injury. Currently, the clinical treatment is less than ideal. Our goal is to develop a combination therapy based on individualized medicine to reduce spasticity after spinal cord injury. In this study, rats received a severe contusive injury at the T9 segment of the spinal cord, followed by gene therapy with adenoassociated virus encoding human neurotrophic factor 3 (AAV-NT3) and a 2-week exercise program starting at 4 weeks after injury. We quantified the frequency of spasms during a swimming test at 4 and 6 weeks after injury and confirmed the results of the swimming test by measuring the H-reflex of the plantar muscle. We obtained weekly hind limb exercise scores to assess the effect of the interventions in hind limb motor function improvement. Then, we used immunofluorescence to observe the immunoreactivity of spinal motor neurons, synaptophysin, cholinergic interneurons, and GABAergic interneurons. We also measured the expression of KCC2 in the spinal cord by western blot. We found that AAV-NT3 gene therapy, exercise, and combination therapy all attenuated the frequency of spasms in the swimming test conducted at 6 weeks after spinal cord injury and increased rate-dependent depression of H-reflex. Combination therapy was significantly superior to AAV-NT3 alone in protecting motor neurons. Recovery of KCC2 expression was significantly greater in rats treated with combination therapy than in the exercise group. Combination therapy was also significantly superior to individual therapies in remodeling spinal cord neurons. Our study shows that the combination of AAV-NT3 gene therapy and exercise can alleviate muscle spasm after spinal cord injury by altering the excitability of spinal interneurons and motor neurons. However, combination therapy did not show a significant additive effect, which needs to be improved by adjusting the combined strategy.